Diachronic treebanks for historical linguistics - Eckhoff, Hanne Martine; Luraghi, Silvia, 1958-; Passarotti, Marco (Benjamins current topics ;, 2020)
"Over the last few decades, the widespread diffusion of digital technology has increased availability of primary textual sources, radically changing the everyday life of scholars in the humanities, who are now able to access, query and process a wealth of empirical evidence in ways not possible before. Also for ancient languages, corpora enhanced with increasingly complex layers of metalinguistic information, such as part-of-speech tagging and syntactic annotation (called 'treebanks') are now available. In particular, diachronic treebanks, which provide data for a language across several historical stages of a given language, allow for a new approach to diachronic studies of syntactic phenomena where scholars previously had to content themselves with empirical work on a much smaller scale. This volume brings together a set of papers that report research on various diachronic matters supported by evidence from diachronic treebanks. The contents of the papers cover a wide range of languages, including English, French, Russian, Old Church Slavonic, Latin and Ancient Greek. Originally published as special issue of Diachronica 35:3 (2018)"--